Expansion of the distribution of Antemna Rapax Stal 1877 (Mantodea: Mantidae) in Panama, Costa Rica and Nicaragua - Santos-Murgas, Alonso (2025)
The praying mantis Antemna rapax Stål, 1877 (Mantidae: Antemninae) is recorded for the first time from several localities in Panama, formally expanding its known distribution within the country. New records come from Konsenda San Blas along the road to San Blas (Guna Yala), Chepo (Panamá Province), El Valle de Antón (Coclé Province), and Santa Fé National Park (Veraguas Province). Additionally, a yellowish coloration pattern observed in females of this species is documented for the first time, with no previous reports from Panama, Costa Rica, or Nicaragua. This chromatic pattern was identified through citizen science platforms such as iNaturalist and GBIF, from which a total of 67 records were extracted. In Costa Rica, data span from 1988 to 2025, and in Nicaragua from 2001 to 2009. The morphology of the ootheca is also described for the first time, along with new biological and ecological data on A. rapax that had not been previously reported in scientific literature.